Pygmy Marmoset Exudate Feeding Stimulates Exudate Production - Jackson, Colin P; Reichard, Ulrich H (Folia primatologica, 2021)
Exudates are an important renewable resource for many primates. Exudate renewability is based on observations of primates repeatedly depleting exudate sites and measures of exudate trees’ daily replenishment rates, but the role of the consumer in the renewal process is unclear. Trees’ exudate production may be independent of the consumer, remaining unchanged regardless of depletion frequency, but since trees produce exudates as a physiological response to fungal infection, they may produce more exudates with more frequent depletion. To test these competing hypotheses, we employed a within-subjects experimental design in which we exposed pygmy marmosets’ exudate holes to two treatment conditions: collecting exudates after 5 h and collecting exudates every hour for five consecutive hours. To compare production outputs between treatments, we used generalised linear mixed modelling in which log-transformed production data were a function of treatment with exudate holes nested within trees as a random effect. The model indicated that the cumulative production of hourly exudate removal was significantly greater than the amount accumulated after 5 h. Furthermore, the random effect of holes nested within trees had the greatest impact on variation in differences between treatments, but another unknown source also contributed to the observed variation. These results support the hypothesis that consumers partly drive exudate production, and although it is unknown what other factors, such as fungal load and healing trajectory, may influence variation between treatments, we conclude that pygmy marmosets can stimulate exudate production by consuming exudates.